The impact of print media on the relationship between Indian Muslims and the Ottoman Empire 1857-1924 - FAZLI PÜSKÜL, (Al-Qanṭara, 2024)
This study focuses on the influence of print media as it examines the complex connection between Indian Muslims and the Ottoman Empire between 1857 and 1924. This study clarifies the interaction of political, cultural, and religious components via the prism of newspapers, pamphlets, and publications written by Ottoman authors. The period is characterized by revolutionary worldwide events. Examining the political participation, the study shows how print media shaped political coalitions and important events like the Khilafat Movement. Additionally, the study emphasizes how print media promoted cross-cultural dialogue by highlighting shared narratives that shaped a shared cultural identity. The study highlights the Ottoman Empire's deliberate attempts to sway Indian Muslims by exposing its clever use of print media. This research fills a major vacuum in the literature by shedding light on the historical processes that influenced transnational Muslim identities and alliances at this pivotal time.